PSAK 68 MEASUREMENT OF FAIR VALUE IFRS CONVERGENCE Fair Value Concept - Maulidah, Sindi; Noviyani, Lisma; Uzliawati, Lia (Review of Accounting and Taxation, 2024)
Abstract Purpose - This study aims to find out about the concept of fair value in PSAK 68: IFRS Convergence Fair Value  Measurement, as a substitute for book value. The convergence of the application of new accounting  standards is oriented towards the International Financial Reporting Standard (IFRS) issued by the  International Accounting Standard Boards (IASB). In this new accounting standard, the concept of  fair value is emphasized more than the concept of book value. This is what makes the difference and  triggers this convergence to change the simpler book value model Design/methodology/approach - This study uses a descriptive  qualitative method with a literature study approach on fair value measurement. Finding - The result of this study  is the concept of fair value (fair value) that is currently considered to have an advantage over book  value is a concept that is widely applied all over the world, as well as with accounting in Indonesia  should be ready to apply the concepts of reasonable value in its accounting standards Originality – Paper Type – Research Paper